Islamic Financial Intermediation in Kuwait Finance House Malaysia: A Fiqh Maqasid Study - Khaled Mohamed Abdullah; Ahmad Wifaq Mokhtar (Universiti Sains Islam Malaysia, 2024)
This article aims to study the financial intermediation in Islamic banks, in term of the degree of extent and achievement according to Islamic rules and Maqasid of Shariah. The objectives of this study has been done theoretically and practically through the study of some applications on the light of Maqasid. This study shows that the financial intermediation achieving the Magasid of Shariah without contradiction if it is applied correctly. Practically, this study was applied on the Kuwait Finance House Malaysia. Results show that Islamic intermediation implementing the Maqasid of Shariah in some aspects, however the study also highlights that the practice of some types of fictitious contracts like Tawaruq, Mudarabah with Tawaruq, lease and sublease, seem to contradict the Islamic rules of the Shariah and its Maqasid. This study recommends the avoidance of fictitious contracts, and to replace them with direct investment according to the comprehensive Islamic banking model of the Islamic banking system.